Connexin Mutants Cause Cataracts Through Deposition of Apatite - Minogue, Peter J.; Sommer, Andre J.; Williams, James C.; Bledsoe, Sharon B.; Beyer, Eric C.; Berthoud, Viviana M. (Frontiers in Cell and Developmental Biology, 2022)
Cataracts are lens opacities that are among the most common causes of blindness. It is commonly believed that cataracts develop through the accumulation of damage to lens proteins. However, recent evidence suggests that cataracts can result from calcium ion accumulation and the precipitation of calcium-containing salts. To test for the presence of precipitates and to identify their components, we studied the lenses of mice that develop cataracts due to mutations of connexin46 and connexin50. Micro-computed tomography showed the presence of radio-dense mineral in the mutant lenses, but not in wild-type lenses. Three-dimensional reconstructions of the scans showed that the distribution of the radio-dense mineral closely paralleled the location and morphology of the cataracts. The mutant lens homogenates also contained insoluble particles that stained with Alizarin red (a dye that stains Ca2+ deposits). Using attenuated total internal reflection micro–Fourier transform infrared spectroscopy, we identified the mineral as calcium phosphate in the form of apatite. Taken together, these data support the novel paradigm that cataracts are formed through pathological mineralization within the lens.